Researching (Homo) Sexualities: Working with Military and War Archives - Koureas, Gabriel (My University, 2016)
When I began my research into the representations of masculinity and sexuality in the visual culture of 1920s Britain in relation to the commemoration of the First World War, I set out for my first visit to the archives of the Imperial War Museum where I had the false notion that in the archival space of the museum I would have been able to find with great ease diaries, memoirs, letters and documents that would very clearly provide the evidence for my research. I arrived at the archive equipped for battle, like the soldiers I was going to research, with all the questions I wanted to ask the archivist. My first question of course was if there are any documents relating to homosexuality, to which question the archivist replied monosyllabically: ‘None’. An ‘archive fever’ suddenly enveloped me. As Jacque Derrida (1995: 57) argues in his essay of the same title, this ‘archive fever’, the mal d’archive, the archive sickness, is more precisely described as en mal d’archive, in need of archives. Derrida eloquently describes this state of all consuming anxiety, in which one burns ‘with a passion’, that does not allow ‘to rest searching for the archive right where it slips away’. This ‘compulsive, repetitive and nostalgic desire’ is for Derrida the desire to ‘return to the origin, a homesickness, a nostalgia for the return to the most archaic place of absolute commencement’.
Keywords: Sexuality; Visual culture; Homosexuality